4, 6, 4′‐trimethylangelicin shows high anti‐proliferative activity on DU145 cells under both UVA and blue light. (10th January 2018) - Miolo, G.; Sturaro, G.; Cigolini, G.; Menilli, L.; Tasso, A.; Zago, I.; Conconi, M. T.
Abstract: Objectives: Furocoumarins (psoralens and angelicins) have been already used under ultraviolet A light (UVA) for the treatment of skin diseases and cutaneous T‐cell lymphoma. Besides their high anti‐proliferative activity, some severe long‐term side effects have been observed, for example genotoxicity and mutagenicity, likely strictly related to the formation of crosslinks. It has been demonstrated that blue light (BL) activation of 8‐methoxypsoralen, an FDA‐approved drug, leads to less mutagenic monoadducts in the DNA. So far, in this work the less toxic and more penetrating BL is proposed to activate 4, 6, 4′‐trimethylangelicin (TMA), an already known UVA photoactivatable compound. Materials and methods: Photocleavage, crosslink formation and oxidative damage were detected in pBR322 plasmid DNA treated with 300.0 μmol/L TMA activated with various exposures of BL. Anti‐proliferative activity, reactive oxygen species (ROS) formation and activation status of some signalling pathways involved in cell growth and apoptosis were verified on DU145 cells treated with 5.0 μmol/L TMA plus 2.0 J/cm 2 of BL. Results: Under BL‐TMA, no mutagenic crosslinks, no photocleavage and neither photooxidative lesions were detected on isolated plasmid DNA. TMA showed high anti‐proliferative activity on DU145 cells through induction of apoptosis. Besides ROS generation, the proapoptotic effect seemed to be related to activation of p38 and inhibition of p44/42 phosphorylation. Interestingly, the decrease in nuclear β‐catenin was coupled with a significant dropping of CD44‐positive cells. Conclusion: Overall, our results indicate that TMA can be activated by BL and may be considered for targeted phototherapy of prostate cancer lesions.